Tapping the Sudanese sorghum germplasm for drought tolerance - Ahmed, Awad Elkarim; Ibrahim, Abu Elhassan; El zain, Ibrahim (Gezira Journal of Agricultural Science, 2011)
Two hundred and ten, seventy four, twenty four and eleven genotypes of sorghum were evaluated in 2001, 2002, 2003 and 2004, respectively, under full and partial irrigation at Gezira Research Farm, Wad Medani, Sudan. The experiment was arranged in a randomized complete block design with three replicates. The objectives of this study were to estimate the variability and genotype-environment interaction. Significant differences were detected among genotypes for the studied characters under both types of irrigation in almost all seasons. Stem borer damage was highly significantly affected by watering regimes, however, partial irrigation reduced stem borer damage. Genotypes PI 568329 and Yruasha had the least leaf senescence scores while PI 569371 and Yruasha were the least damaged by stem borer. Genotypes PI 563310 (5488 kg/ha) and PI 570851 (5452 kg/ha) outyielded the check varieties Yruasha (4596 kg/ha) and Wad Ahmed (5434 kg/ha). The current study depicted that the variability observed among the genotypes was maintained for most characters under both water regimes. Water stress reduced most of the studied characters but increased number of tillers per plant, lodging and senescence which could be used as selection indices.      تم تقييم مائتين وعشرة سلالة من الذرة الرفيعة موسم 2001، أربعة وسبعون سلالة موسم 2002، أربعة وعشرون سلالة موسم 2003 واحد عشرة سلالة موسم 2004 في مزرعة محطة بحوث الجزيرة بواد مدني, السودان. استخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات تحت ظروف ري كامل وجزئي وذلك لدراسة التباين و تفاعل السلالة مع البيئة. أظهرت النتائج أن هنالك تبايناً معنوياً بين السلالات في معظم الصفات المدروسة تحت الري والجفاف خلال المواسم الأربعة (2001 – 2004). تأثرت الإصابة بثاقبات الساق بمستوي الري فقد إزدادت متأثرة بالجفاف بينما زاد عدد الخلف في النبات، جفاف الأوراق والرقاد. السلالات PI 568329  ويرواشا كانت الأقل جفافاً للأوراق و كانت السلالات الأقل إصابة بثاقبات الساق هي PI 569371 و يرواشا بينما التي تفوقت على الشواهد المتحملة للجفاف  يرواشا ( (4526 kg/ha و ود احمد (kg/ha (5434 في الإنتاجية هي  PI  563310(kg/ha 88(54  و PI 570851 (kg/ha .(5452 أوضحت الدراسة ثبات التباين تحت الري الكامل والجزئي ولكل المواسم. الإجهاد المائي قلل معظم الصفات بينما زاد عدد الخلف للنبات ونسبة الرقاد وجفاف الأوراق لذا يمكن استخدامها كدلائل انتخاب.